A computerized approach for loaded tooth contact analysis of planetary gear drives considering relevant deformations. (April 2018) - Tsai, Shyi-Jeng; Ye, Siang-Yu
Abstract : This paper proposes a computerized approach based on the influence coefficient method to solve the statically indeterminate problem of multiple loaded contact tooth pairs in planetary gear drives. The influences of the deformation on the loaded contact characteristics are divided into three categories according to the relation of the acting load and the deformation on the specific tooth pairs, the gears and the gear pairs, respectively. Not only the contact and bending deformation of the engaged teeth, but also the planet shaft deflection and the twist deformation of the carrier and the sun gear are involved in the model. With discretized contact region of each tooth pair, three-dimensional contact patterns with distributed stresses, including the concentrated stress due to edge effect and tip corner contact, can be simulated. The simulated results are verified to have a good agreement with FEM. A numerical example of a planetary gear set with non-modified flanks and the error-free condition is analyzed in the paper. The effects of the deformation, the variations of the shared loads, the contact stress, the loaded transmission errors, and the contact patterns with the distributed contact stresses in the cases with/without tip corner contact are discussed.